Increased risk of osteoporosis in patients with erectile dysfunction: A nationwide population-based cohort study. Issue 26 (June 2016) - Wu, Chieh-Hsin; Lu, Ying-Yi; Chai, Chee-Yin; Su, Yu-Feng; Tsai, Tai-Hsin; Tsai, Feng-Ji; Lin, Chih-Lung
Abstract : Abstract: In this study, we aimed to investigate the risk of osteoporosis in patients with erectile dysfunction (ED) by analyzing data from the Taiwan National Health Insurance Research Database (NHIRD). From the Taiwan NHIRD, we analyzed data on 4460 patients aged ≥40 years diagnosed with ED between 1996 and 2010. In total, 17, 480 age-matched patients without ED in a 1:4 ratio were randomly selected as the non-ED group. The relationship between ED and the risk of osteoporosis was estimated using Cox proportional hazard regression models. During the follow-up period, 264 patients with ED (5.92%) and 651 patients without ED (3.65%) developed osteoporosis. The overall incidence of osteoporosis was 3.04-fold higher in the ED group than in the non-ED group (9.74 vs 2.47 per 1000 person-years) after controlling for covariates. Compared with patients without ED, patients with psychogenic and organic ED were 3.19- and 3.03-fold more likely to develop osteoporosis. Our results indicate that patients with a history of ED, particularly younger men, had a high risk of osteoporosis. Patients with ED should be examined for bone mineral density, and men with osteoporosis should be evaluated for ED. Abstract : Supplemental Digital Content is available in the text